Mobile ad hoc networks - current approaches and future directions. - Weniger, K. (IEEE Network : the magazine of global information exchange)
Most research efforts in the area of MANETs focus on developing efficient routing protocols. Although routing protocols assume unique node addresses, the question of how to provide them remains open. In order to allow truly spontaneous and infrastructureless networking, a protocol for dynamic allocation of unique addresses is needed. Recently, various address autoconfiguration protocols for MANETs have been proposed. This article gives an overview of the challenges of address autoconfiguration in MANETs, presents current approaches, and discusses their advantages and drawbacks.